Integrating Fiqh Principles In The Sustainable Development Goals (SDGs) Economy: Increasing Sustainable And Inclusive Economic Growth - Syafrida Syafrida; Musmulyadi Musmulyadi; Nurnaningsih Nurnaningsih; Andi Masniah (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2023)
The purpose of this study is to analyze the Fiqh principles in the Sustainable Development Goals (SDGs) in promoting sustainable and inclusive economic growth. In this research used research literature review. This research shows that the integration of Fiqh principles into the Economic Sustainable Development Goals (SDGs) can increase sustainable and inclusive economic growth. Fiqh principles have their own uniqueness and advantages in providing their own views in building a sustainable and inclusive economy. In this case, efforts are needed to build a fair and sustainable economy by considering environmental, social and economic aspects in a balanced manner, as well as reducing the excessive use of resources and increasing the efficiency of their use. In addition, it is also necessary to encourage the development of environmentally friendly and sustainable technologies, and develop an integrated and sustainable environmental management system.